On-chip liquid sensing using mid-IR plasmonics - Hinkov, B.; David, M.; Strasser, G.; Schwarz, B.; Lendl, B. (Frontiers in Photonics, 2023)
The investigation of molecules in the mid-IR spectral range has revolutionized our understanding in many fields such as atmospheric chemistry and environmental sensing for climate research or disease monitoring in medical diagnosis. While the mid-IR analysis of gas-samples is already a mature discipline, the spectroscopy of liquids is still in its infancy. However, it is a rapidly developing field of research, set to fundamentally change our knowledge of dynamical processes of molecules in liquid-phase. In this field, mid-IR plasmonics has emerged as breakthrough concept for miniaturization, enabling highly-sensitive and -selective liquid measurement tools. In this review, we give an overview over current trends and recent developments in the field of mid-IR spectroscopy of molecules in liquid phase. Special attention is given to plasmon-enhanced concepts that allow measurements in highly compact sensor schemes. Nowadays, they reach full monolithic integration, including laser, interaction section and detector on the same chip, demonstrating unprecedented operation in in situ and real-time analysis of chemical processes.